"Undeserved" Grades or "Underserved" Students? Faculty Anxieties and Eroding Standards in the Corporate University (Higher Education Politics and Economics, 2023)
Unsustainable student debt and a precarious labor market continue to raise public doubts over the value of a college degree. Observers note decades of grade inflation, eroding confidence in academic standards.  Yet little attention has been paid to the perceptions of professors themselves. This report fills the gap by surveying 223 tenured professors in U.S. public universities. We query faculty on sensitive questions central to debate over academic standards. Results show a substantial fraction of professors affirms the serious problems of grade inflation and declining standards. Moreover, political orientation is the best predictor of where faculty stand on these delicate questions. We close by encouraging viewpoint diversity in higher education and greater self-awareness among liberal faculty of our collective biases.